Methanesulfonic acid (MSA) in clean processes and applications: a tutorial review - Binnemans, Koen; Jones, Peter Tom (Green chemistry : an international journal and green chemistry resource : GC, 2024)
This Tutorial Review acquaints chemists and metallurgists with the properties and industrial applications of methanesulfonic acid (MSA, CH SO H). Over the past quarter-century, MSA has garnered increasing interest as a reagent for green chemistry due to its strong acidity, while circumventing many of the challenges associated with handling concentrated sulfuric acid, hydrochloric acid, or nitric acid. Concentrated MSA is a non-oxidizing reagent, exhibiting high chemical stability against redox reactions and hydrolysis, as well as high thermal stability and limited corrosivity towards construction materials. It is colorless, odorless, and possesses a very low vapor pressure. MSA combines commendable biodegradability with low toxicity. It is extensively utilized as a Brønsted acid catalyst for esterification or alkylation reactions, and is employed in biodiesel production. The high solubility of its metal salts, the high electrical conductivity of its concentrated solutions, coupled with the high electrochemical stability of MSA and its anion, make MSA-based electrolytes beneficial in electrochemical applications. Examples include the electrodeposition of tin-lead solder for electronic applications and the high-speed plating of tin on steel plate for food cans. MSA-based electrolytes are used in redox flow batteries (RFBs). MSA offers a much safer and environmentally friendlier alternative to electrolytes based on fluoroboric or fluorosilicic acid. A novel application area is as a strong acid in extractive metallurgy, where it may contribute to the development of circular hydrometallurgy. MSA is being explored in lithium-ion battery recycling flowsheets, as well as in other applications in the field of metal recovery and refining. However, this review is not solely about the advantages of MSA for green chemistry or clean technologies, as there are also some potential drawbacks. Apart from its higher price compared to regular strong acids, MSA has only minor advantages for applications where sulfuric acid performs well. Since methanesulfonate biodegrades into sulfate, the same emission restrictions as for sulfate should be considered. In conclusion, MSA is the acid of choice for applications where metal sulfates cannot be used due to poor solubility or where concentrated sulfuric acid is too reactive towards organics.